KONSELING KEWIRAUSAHAAN (ENTREPRENEURSHIP COUNSELING) - Mochamad Edwar (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2018)
Today, university unemployment in Indonesia is increasing. According to BPS (2016) the number of unemployed college graduates there are 800 thousand people. While the formation to become civilian government officials in the presence of a moratorium applied by the government is increasingly limited. Similarly, the opportunity to become an employee in the government-owned enterprises and local enterprises is increasingly limited and the level of competition is getting tighter. Therefore Kemenristek Dikti programming entrepreneurship so that students and graduates want to entrepreneurship since still be student and after graduated from college. According to the United Nations 2% of the total population of a State shall entrepreneurship if it wishes that the population of the State is prosperous. On the one hand we expect students or college graduates to be willing, eager, or interested to entrepreneurship, but on the other hand there are still students who have not entrepreneurship for reasons not having enough capital, no experience, not creative and innovative, not dare to bear the risk etc. This student mindset is known after a preliminary interview with students to find out the reason they have not or not entrepreneurship. This mindset should be transformed into a positive mindset so that students are motivated to entrepreneurship from college or after college. This effort the authors do by doing or providing entrepreneurship counseling (counseling) through counseling interviews with students to change the mindset that can be a problem for them to entrepreneurship. Keywords— Counseling, Entrepreneurship